2019
DOI: 10.1136/emermed-2018-208329
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of adolescent trauma in England: a review of TARN data 2008–2017

Abstract: ObjectivesTrauma contributes significantly to adolescent morbidity and mortality. We aimed to ascertain the epidemiology of adolescent trauma to inform prevention strategies.MethodsData were abstracted from TARN (Trauma Audit Research Network) from English sites over a 10-year period (2008–2017). Adolescents were defined as 10–24 completed years. Descriptive statistical analysis was used in this study.ResultsThere were 40 680 recorded cases of adolescent trauma. The majority were male (77.3%) and aged 16–24 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…The comparison with other studies on patterns of trauma was limited by the differences in population samples, methods of data collection, number of hospitals involved in the analyses and timeframes taken into account. However, the review of recent literature [10][11][12][13][14][15][16] provided interesting elements of analysis. The incidence of injuries following road traffic collisions has been increasing globally in the last two decades [10], with the exception of countries with high socio-demographic index (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparison with other studies on patterns of trauma was limited by the differences in population samples, methods of data collection, number of hospitals involved in the analyses and timeframes taken into account. However, the review of recent literature [10][11][12][13][14][15][16] provided interesting elements of analysis. The incidence of injuries following road traffic collisions has been increasing globally in the last two decades [10], with the exception of countries with high socio-demographic index (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The age group of young adults (14–39 years old) includes the years of adolescence, between 14 and 20 years of age [ 18 ]. Adolescence is characterized by “reduced self-control, increased risk-taking behaviors and experimentation with alcohol and drugs” [ 16 ]. Roberts et al[ 16 ] observed evidence of alcohol and drugs abuse in 20% adolescent trauma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this field, motor vehicle collisions (MVCs) represent one of the main causes of death among 14- to 19-year-olds worldwide [ 4 , 5 , 6 ], who constitute the population most at risk even of nonfatal MVCs. Epidemiological studies on adolescents’ road collisions have reported a rate of prevalence of approximately of 50% [ 7 , 8 , 9 ], with important consequences for their psychological and physical well-being [ 10 , 11 , 12 ]. Most studies have shown a higher prevalence of injuries and road accidents among males [ 13 , 14 , 15 , 16 , 17 ], and results concerning females in relation to road accidents are few and inconsistent [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…[12] Of note, Ireland has a significantly lower rate of violent injuries in the 10-15 year group when compared to England and the rates of stabbing were 0.2% in Ireland vs 3% in England. [13] Overall, It was reassuring in our study that despite the prevalence of multiply injured patients and the high rate of operative intervention in this cohort, 94.9% of patients suffering major trauma are discharged home after hospital.…”
Section: Discussionmentioning
confidence: 53%